KUFRI HIMSONA: A CHIPPING CULTIVAR FOR HILL REGIONS OF INDIA - Pandey, S. K.; Singh, S. V.; Kumar, Dinesh; Manivel, P.; Marwaha, R S; Kumar, Parveen; Singh, B. P.; Gupta, V. K. (Potato Journal, 2013)
The variety Kufri Himsona has been developed to provide processing quality potatoes from highlands at a time when fresh potatoes from plains are not available. This variety, tested at different locations in highlands, has shown excellent processing quality, both in the laboratory tests and industrial frying. Kufri Himsona gives high total and processing grade tuber yields and possesses field resistance to late blight. Its round-oval tubers contain high dry matter (22.4%), low reducing sugars (<100 mg/100 g fr wt) and are free from internal defects. Kufri Himsona is expected to be a good replacement for the variety Kufri Jyoti, as it will be possible for hill farmers to market the produce both for processing and table purposes.